Acceptance and commitment therapy (ACT) counseling as non-suicidal self-injury (NSSI) intervention for students - Afra Hasna; Nurul Fajri (Jurnal Konseling dan Pendidikan, 2023)
Non-Suicidal Self-Injury (NSSI) behavior is carried out as an effort to avoid thought, feeling, somatic sensation or other internal experiences that are uncomfortable or troublesome. The intervention carried out using Acceptance and Commitment Therapy (ACT) to increase psychological flexibility targeted at avoiding experiences or tendencies to avoid unwanted thoughts or emotions. This research aims to provide NSSI behavioral intervention which is carried out using the Acceptance and Commitment Therapy (ACT) as an effort to change positive behavior through a process of acceptance, attention and behavior change. The population in this research is students of SMAN 1 Bogor and the sample was taken using purposive sampling technique with the characteristics of conducting NSSI for 1 year, so three people are selected as samples who have met the criteria. This research is designed using single subject research with the ABA model and analyzed using inferential statistics. By using the Difficulties in Emotion Regulation (DERS) instrument, the results obtained in the baseline phase (A1) are an average score of 99.6; intervention phase (B) obtained an average score of 80.9; and at baseline (A2) an average score of 63.8 is obtained. This means that there is a decrease in the graph of NSSI behavior at each intervention session using ACT. This research provides information that using (ACT) can reduce NSSI behavior in students.